2021
DOI: 10.1021/acs.analchem.0c04446
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Nanolocal Polymer and In Situ Readout Unit Placement in Mesoporous Separation Layers

Abstract: Bioinspired solid-state nanopores and nanochannels have attracted interest in the last two decades, as they are envisioned to advance future sensing, energy conversion, and separation concepts. Although much effort has been made regarding functionalization of these materials, multifunctionality and accurate positioning of functionalities with nanoscale precision still remain challenging. However, this precision is necessary to meet transport performance and complexity of natural pores in living systems, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In further work, it was demonstrated that polymerization is indeed initiated via the photochemical mechanism and not by local temperature increase or hot electrons under the applied low irradiation energy. 50 Our research group 48,51,52 applied dye-sensitized visible-light induced photopolymerizations using a dye-tertiary amine photosensitizer, photoinitiator combination for mesoporous silica functionalization resulting in polymer-dominated gating of ionic mesopore accessibility. By using surface plasmons localized polymer functionalization in mesoporous layers was achieved (Fig.…”
Section: Free Radical Polymerizations Initiated By Visible Lightmentioning
confidence: 99%
“…In further work, it was demonstrated that polymerization is indeed initiated via the photochemical mechanism and not by local temperature increase or hot electrons under the applied low irradiation energy. 50 Our research group 48,51,52 applied dye-sensitized visible-light induced photopolymerizations using a dye-tertiary amine photosensitizer, photoinitiator combination for mesoporous silica functionalization resulting in polymer-dominated gating of ionic mesopore accessibility. By using surface plasmons localized polymer functionalization in mesoporous layers was achieved (Fig.…”
Section: Free Radical Polymerizations Initiated By Visible Lightmentioning
confidence: 99%
“…This can be used to in situ follow the polymer formation within mesoporous films limits. 207 The next steps will of course point towards asymmetric plasmonic nanoparticles, their stable integration into mesoporous films and their use for polymer placement and sensing.…”
Section: Transport Direction Via Asymmetric Nanopore Architecturementioning
confidence: 99%